Guru Bukan Tukang Ketik: Mengembalikan Esensi Supervisi melalui Integrasi Data Digital - Pitri Pardomuan; Renaningtyas Putri Lestari; Anggun Dwi Andriani; Erdi Saputra; Miftahir Rizqa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Educational supervision is an important instrument for improving learning quality and teacher professionalism. However, its implementation is often dominated by administrative activities that emphasize document completion rather than reflective and collaborative professional development. This study aims to analyze the integration of digital data in restoring the essence of educational supervision to become more objective, effective, reflective, and collaborative. The research employed a literature review with a descriptive qualitative approach by examining relevant scientific sources on educational supervision and digital transformation. The findings indicate that digital data–based supervision enhances the objectivity of teacher performance assessment, supports more accurate decision-making, and improves the quality of feedback in the learning process. In addition, digital data integration promotes a shift from administration-oriented supervision toward a reflective, collaborative, and data-driven approach, enabling teachers to participate actively in evaluating and improving their instructional practices. This approach also reduces teachers’ administrative workload and increases supervision efficiency within educational institutions. Therefore, digital data integration contributes significantly to transforming educational supervision into a sustainable professional development system that is adaptive to technological advancement and supports improved teacher professionalism and educational quality in the digital era.